Supporting Job Creation and Innovation through MSME Development in MENA - McConaghy, Peter (World Bank, Washington, DC, 2013)
Employment generation is a critical challenge facing policymakers in the Middle East and North Africa (MENA) region, particularly since the Arab uprisings as citizens challenge governments to provide greater economic and social opportunities. Unemployment levels in MENA are above those of any other region, while the labor force participation rate remains stubbornly low. Three out of four working-age women do not participate in the labor force, constituting 80-90 percent of MENA's inactive workers. Unemployment is further complicated by the demographic bulge the region is facing. The lack of good employment opportunities in the region is reflected in high levels of informality: in no MENA country does the formal private sector employ more than 20 percent of workers. In recent years, policymakers have prioritized developing Micro, Small, and Medium-Sized Enterprises (MSMEs) to address the employment challenge in MENA. A small proportion of high performing MSMEs have the potential to grow into internationally competitive companies, generating significant economic benefits through raised productivity, employment, and economic stability. Addressing the employment challenge in MENA requires a coordinated set of policy interventions that combine access to finance for MSMEs with direct business development services, early stage investment for new firms, and broader reforms to the business regulatory and legal environment.